Increase the risk of intellectual disability in children with scabies: A nationwide population-based cohort study. Issue 23 (June 2017) - Liu, Jui-Ming; Hsu, Ren-Jun; Chang, Fung-Wei; Yeh, Chia-Lun; Huang, Chun-Fa; Chang, Shu-Ting; Chiu, Nan-Chang; Chang, Hung-Yang; Chi, Hsin; Lin, Chien-Yu
Abstract : Abstract: Scabies is a common and distressing disease caused by the mite Sarcoptes scabiei var. hominis . Psychiatric disorder in childhood is an important disease and easily neglected. There are several similarities in scabies and psychiatric disorders in childhood (PDC). Both of them may present with pruritus. They are relatively common in patients with lower socioeconomic status and crowded environment. Furthermore, immune-mediated inflammatory processes play a role in the pathophysiology in both diseases. An association between scabies and psychiatric disorders may exist. This nationwide population-based cohort study utilized data from the National Health Insurance Research Database to investigate the relationship between scabies and PDC. A total of 2137 children with scabies were identified as the study group and 8548 age- and sex-matched children were selected as the control group. A total of 607 (5.68%) children developed PDC during the 7-year follow-up period. The overall incidences of PDC are similar but patients with scabies had a higher risk of developing intellectual disability (ID) (scabies group vs control group: 1.3% vs 0.6%, adjusted hazard ratio: 2.04 and 95% confidence interval: 1.25–3.32). The immune-mediated inflammatory processes of both diseases were reviewed and may contribute to the 104% increased risk of interleukin in patients with scabies. We suggest a more comprehensive management in treating patients with scabies or ID. Early and comprehensive treatment of scabies and other risk factors may decrease the risk of subsequent ID. When we approach patients with ID, concurrent evaluation of scabies and other risk factors may contribute to successful management.